2002
DOI: 10.1096/fj.01-0577com
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of p53 activity and inhibition of neural cell proliferation by glucocorticoid receptor activation

Abstract: In analyzing the molecular mechanisms underlying glucocorticoid-induced apoptosis in neural cells, we observed that dexamethasone, by activating glucocorticoid receptors, causes arrest of HT-22 cells in the G1 phase of the cell cycle; upon withdrawal of the agonist, cells resume proliferation. Our investigations revealed that glucocorticoid treatment, although having no effects on endogenous p53 protein stability, induces rapid translocation of p53 to the nucleus and enhances its transcriptional activity. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
52
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 84 publications
9
52
0
2
Order By: Relevance
“…Therefore, indirect regulation of Bnip3 gene transcription through glucocorticoid modulation of NF-κB remains a possibility. Conversely, Bnip3 gene transcription appears to be independent of p53 activity (Guo et al, 2001, Fei et al, 2004, despite reports of glucocorticoid regulation of p53 (Crochemore et al, 2002).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, indirect regulation of Bnip3 gene transcription through glucocorticoid modulation of NF-κB remains a possibility. Conversely, Bnip3 gene transcription appears to be independent of p53 activity (Guo et al, 2001, Fei et al, 2004, despite reports of glucocorticoid regulation of p53 (Crochemore et al, 2002).…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, activated GR directly regulates Bnip3 gene transcription via a GRE site within the Bnip3 promoter. Notwithstanding, earlier studies show that glucocorticoids can act indirectly to regulate expression of the Bcl-2 gene family by modulating NF-κB (Ramdas andHarmon, 1998, Dhandapani et al, 2005) and p53 transcriptional activity (Miyashita et al, 1994, Miyashita and Reed, 1995, Maiyar et al, 1997, Crochemore et al, 2002, Iyer et al, 2003. Bnip3 expression has similarly been shown to be attenuated following inhibition of NF-κB (Baetz et al, 2005), a gene that is glucocorticoid regulated (Webster and Cidlowski, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Further, the apoptotic effects of DEX were previously shown to be blocked with a GR antagonist; 36 GR are transcription factors and we have previously shown that their activation by DEX can trigger a molecular death cascade in the hippocampus and cell cycle arrest in a neural cell line. 13,25 The issue of whether DEX acts directly on neurons to stimulate their demise cannot be resolved easily in vivo. We therefore attempted to address this question in primary neuronal cultures derived from early postnatal rats.…”
Section: Discussionmentioning
confidence: 99%
“…For GR Western blots, cells were lysed, processed and evaluated using semi-quantitative densitometry as described previously. 25 …”
Section: Reverse-transcriptase Pcrmentioning
confidence: 99%
“…Images are representative of three experiments with consistent results proliferation. 30 Moreover, experiments using antisense p53 oligonucleotides show that blocking p53 expression reverses DEX-induced p21 upregulation and inhibition of proliferation. 31 Furthermore, p53 was recently found to be involved in GR-mediated repression of nuclear factor-kB transcription.…”
mentioning
confidence: 99%